Peningkatan Akreditasi Jurnal Nasional bidang Studi Islam - Nadjih, Difla; Santoso, Fattah S.; Muthmainnah, Muthmainnah; Hermawan, Toto; Rahman, Ahmad Syafii; Rahayu, Supriati Hardi; Arifin, Zainul; Nasruddin, Muhammad (Universitas Cokroaminoto Yogyakarta, 2023)
The purpose of this activity is to describe the implementation of the preparation of the Ulumuddin Journal: Journal of Islamic Studies or UJII from FAI UCY to become an Islamic studies journal that has increased its level of accreditation. In it there are several activities that are summarized in the UJII National Journal Accreditation Improvement Program which are based on the findings in the self-evaluation of the journal in the field of Islamic studies itself. A number of Journal activities based on the Open Journal System (OJS) version 3 have had an impact on journals and faculties that oversee their management.